2012
DOI: 10.2106/jbjs.st.k.00037
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrical Costal Osteochondral Autograft for Reconstruction of Large Defects of the Capitellum Due to Osteochondritis Dissecans

Abstract: Background: There is a need to clarify the usefulness of and problems associated with cylindrical costal osteochondral autograft for reconstruction of large defects of the capitellum due to osteochondritis dissecans. Methods: Twenty-six patients with advanced osteochondritis dissecans of the humeral capitellum were treated with use of cylindrical costal osteochondral autograft. All were males with elbow pain and full-thickness articular cartilage lesions of ‡15 mm in diameter. Clinical, radiographic, and magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(94 citation statements)
references
References 28 publications
0
92
0
2
Order By: Relevance
“…Potential surgical interventions include arthroscopic removal of loose bodies, abrasion chondroplasty, retrograde drilling, microfracture, in situ fixation, osteochondral autograft transplantation system (OATS), and costal osteochondral transplantation (COT) [5][6][7]10 …”
Section: Operative Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Potential surgical interventions include arthroscopic removal of loose bodies, abrasion chondroplasty, retrograde drilling, microfracture, in situ fixation, osteochondral autograft transplantation system (OATS), and costal osteochondral transplantation (COT) [5][6][7]10 …”
Section: Operative Treatmentmentioning
confidence: 99%
“…The procedure entails harvesting a costal osteochondral fragment with hyaline cartilage, usually from the sixth rib, for transplantation into the recipient site on the capitellum [5,42]. Zlotolow and Bae revealed that the costal hyaline cartilage layer is much thicker than in OATS grafts and must be trimmed in order to fit flush.…”
Section: Costal Osteochondral Transplantationmentioning
confidence: 99%
See 3 more Smart Citations